Canada : 2016 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2016)
This paper describes recent economic developments, outlook, risks, and policy challenges of the Canadian economy. After almost two years, the effects of the oil price shock continue to reverberate through the Canadian economy. Growth has decelerated, but inflation expectations remain well anchored. With the slowdown in growth, the output gap has reopened. Persistently low energy prices pose an important risk to the economy. The banking system remains sound, but exposure to the oil and gas sector will require higher provisions against expected losses. The policy mix over the near-term should cushion the adverse effects of lower oil prices on the economy while safeguarding financial stability.